Providing medical care by family doctors in family planning services and prevention of unwanted pregnancies - O. S. Shcherbinska; H. O. Slabkyi (Publishing House TRILIST, 2020)
Purpose of the study: to identify the types of medical services for family planning and prevention of unwanted pregnancies that should be provided by family doctors, and competencies they should have to provide, as well as to identify benefits and possible risks for family planning services at the primary level. Materials and methods. 50 obstetricians and gynecologists and 50 family doctors were interviewed as experts with the help of a specially designed questionnaire. Research results were analyzed using the method of structural-logical analysis. Results. The list of medical services for family planning and prevention of unwanted pregnancies to be provided by family doctors includes: formation of safe sexual behavior in adolescents and young people, formation of responsible attitude to reproductive health in adolescent girls, explanation to married couples about use of barrier contraception and emergency contraception immediately after sexual intercourse, information activities aimed at promoting a healthy lifestyle, formation of responsible parenthood, strengthening family and marital relations. The advantages of providing these services at the primary level are increased physical availability of medical care for family planning, possible reduction of unwanted pregnancies, early onset of sexual relations culture and higher opportunities for adolescents to develop a responsible attitude to reproductive health. Among the risks of providing family planning services at the primary level experts noted the low level of professionalism of family doctors and nurses, lack of motivation to provide this area of medical services, low level of interaction between primary and obstetric care services, low public confidence in family doctors. Conclusion. Applying of expertly defined list of services for family planning and prevention of unwanted pregnancies at the primary level of medical care when family doctors acquire the necessary competencies will increase the availability and effectiveness of this type medical care.